Aboriginal population profiles for development planning in the Northern East Kimberley - Taylor, J. (John), 1953-; Australian National University. Centre for Aboriginal Economic Policy Research (Canberra : Centre for Aboriginal Economic Policy Research, 2004)
This study profiles social and economic conditions in the region, focusing on the Aboriginal population. It examines demography, the labour market, income, education and training, housing and infrastructure, health status, and regional involvement in the criminal justice system. It provides a quantum to discussions of need, aspirations and regional development capacities, as well as a benchmark against which the impact of developmental actions may be assessed.
Analytical framework -- Demography of the East Kimberley and Northern East Kimberley -- Aboriginal participation in the regional labour market -- Employment and non-employment income -- Employment and welfare income -- Education and training: participation and outcomes -- Housing and infrastructure -- Health status -- Regional involvement in the Western Australian criminal justice system -- Implications, dilemmas, and the way ahead.
Title from screen page; viewed 9 Aug 2004.
Includes bibliographical references.
Xviii, 124 p. : maps ; 25 cm.
Print version record.
Keywords: Aboriginal Australians -- Australia -- Kimberley (W.A.) -- Population; Aboriginal Australians -- Australia -- Kimberley (W.A.) -- Economic conditions; Aboriginal Australians -- Australia -- Kimberley (W.A.) -- Social conditions; Kimberley (W.A.) -- Economic conditions; Kimberley (W.A.) -- Social conditions; Australiens (Aborigènes) -- Australie -- Kimberley (Austr.-Occ.) -- Population; Kimberley (Austr.-Occ.) -- Conditions économiques.; Kimberley (Austr.-Occ.) -- Conditions sociales; SOCIAL SCIENCE -- Research; Aboriginal Australians -- Economic conditions; Aboriginal Australians -- Population; Aboriginal Australians -- Social conditions; Economic history; Social conditions; Western Australia -- Kimberley; Electronic books; Electronic books; Electronic books